POSITION OF JOINT PROPERTY IN POLYGAMOUS MARRIAGES REVIEWED IN THE MARRIAGE LAW AND THE COMPILATION OF ISLAMIC LAW - Fiqrie, Okky Faitzal; Amalia, Lia; Abas, Muhamad (Universitas Labuhanbatu, 2025)
This research highlights the legal complexity related to the division of joint assets in marriage, both in the context of monogamy and polygamy, with a focus on the provisions of Article 35 paragraph 1 of Law No. 1 of 1974 and Article 65 paragraph (1) point (b) of Law No. 16 2019. Through a normative juridical approach and analytical descriptive methods, this research examines how assets obtained during marriage are recognized as joint assets without considering individual contributions, as well as the implications of the division of assets in polygamous marriages where each wife is entitled to a fair share according to Islamic law. Implementation of this law requires in-depth understanding and consistent enforcement from the relevant parties to ensure justice and harmony within the family.Keywords: Joint Property, Polygamy, Islamic Law